Combined Treatment of Androgen-Independent Prostate Cancer Cell Line DU145 with Chemotherapeutic Agents and Lithium Chloride: Effect on Growth Arrest and/or Apoptosis - Hossein, Ghamartaj (Avicenna Research Institute, 2012)
Hormone-independent prostate cancer cell lines are resistant to antineoplastic drugs, this study sought to determine the usefulness of lithium chloride as an inhibitor of glycogen synthase kinase-3β to increase the cytotoxic effect of doxorubicin, etoposide or vinblastine antineoplastic drugs on DU145 cells. Combination effect was assessed by using low and IC(50) doses of drugs + lithium chloride. Subsequently, cell cycle analysis and p53 levels and its subcellular localization as a key regulator of cell cycle were assessed. Lithium chloride showed cytotoxic effect in a dose and time dependent manner (p<0.001). Both drugs doxorubicin and etoposide in combination with lithium chloride (LiCl) showed higher percent of cells in SubG1 compared to control (p<0.001). Combination of IC(50) dose of doxorubicin and lithium chloride led to S phase arrest (p<0.001, compared to control, lithium chloride or doxorubicin alone). Moreover, G2/M arrest was significantly increased when low dose of doxorubicin and vinblastine were combined with lithium chloride (p<0.001, compared to control and lithium chloride alone). DU145 cells were highly sensitive to vinblastine and no significant changes were observed when combined with lithium chloride. The IC(50) doses of all three drugs combined with lithium chloride demonstrated decreased cell percent in G1 phase compared to control or lithium chloride alone (p<0.001). Moreover, in the presence of lithium chloride there were increased levels of p53 in cytoplasm and nucleus (p<0.05). Our results suggest that combination of lithium chloride with chemotherapeutic agents may increases their cytotoxic effect on hormone non-responsive human prostate cancer cells.